Kajian Bentuk Pengolahan dan Analisis Finansial Buah Api api (Avicennia officinalis L.) sebagai Bahan Makanan dan Minuman di Kabupaten Deli Serdang - Gustinaria Sianturia; Agus Purwoko; Kansih Sri Hartini (Program studi Kehutanan USU, 2013)
This study was aimed to identify the technique of processing, financial feasibility, and business development strategies of Api api fruits (Avicennia officinalis L.) processing at Dusun Paluh Merbau, Tanjung Rejo Vilage,Sub District of Percut Sei Tuan, District of Deli Serdang. The analysis methods used are descriptive analysis, financial analysis, and analysis of the business development strategy by using SWOT analysis. The results showed that the product of processed Api api fruits at Dusun Paluh Merbau are chips, donuts, spongecake and dawet. All kinds of processing are feasible to be developed and have a favorable prospect. It can be seen from the value of R / C ratio which is more than one. Based on the SWOT analysis, the major threat that influence on the development of processing Api api fruits are the absence of permit from the Department of Health and halal certificate’s from MUI to ensure the product is safe for consumption. Key words: Avicennia officinalis, finance analysis, SWOT analysis.